(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
Advanced (Technical) ceramic compounds today play an important role in the development of science and technology, and widely used in many biological, electronic and other applications due to the distinctive characteristics of the materials that are included in its composition. It considered one of the most efficient materials in our time, especially metal ceramic. A series of samples were prepared and incinerated in an atmosphere of air and an inert gas(Argon), The X-Ray diffraction results showed that all samples crystallized according to the Tetragonal system. It formed when doping tin oxide with copper for x= (90, 80, 75, 66.5, 50, 33.5, 25) Statistical ceramics (two phases of SnO2, CuO) and when doping for x=10 that Matrix ceramics are formed (one phase of SnO2). In addition, no difference observed in burning in air and inert atmosphere expect for the presence of traces of SnO in inert atmosphere.